Coming of age in academia: Canadian International Relations and the "optimistic interregnum" of the 1990s. (June 2017) - Gutterman, Ellen
Taking the view of International Relations (IR) as a socio-intellectual space conditioned by historical circumstances, and drawing on my personal reflections on international politics in the 1990s as a particularly important influence on my own professional and intellectual path in IR, this paper explores the 1990s as an exceptional period that shaped the decline of Canadian Foreign Policy as a field of study in Canadian IR. Bookended by the collapse of the Soviet Union and the end of the Cold War, at the beginning, and the start of the War on Terror at its finale, the 1990s can be read as an "optimistic interregnum" during which new possibilities arose for an inclusive, global transnationalism and the global governance of important problems. New ideas and new ways of conceptualizing IR through a global lens emerged. For Canadian students of IR in the 1990s, outward-looking globalism, transnationalism, cosmopolitanism, and theoretical eclecticism fit with the hopeful optimism of the times. In contrast, CFP—with its attendant requisite of policy relevance in service of Canadian national priorities—seemed inward-looking, parochial, and on the sidelines of important new intellectual currents and analyses.